DOP71 Effects of ustekinumab induction therapy on endoscopic and histological healing in the UNIFI Phase 3 study in ulcerative colitis. (25th January 2019) - Li, K; Friedman, J R; Marano, C; Zhang, H; Yang, F; Feagan, B G; Peyrin-Biroulet, L; De Hertogh, G
Abstract: Background: Ustekinumab (UST) is an effective therapy for moderate–severe UC; however, data regarding histological healing and the combination of histological and endoscopic healing (also described as endoscopic improvement in the appearance of the mucosa) are unknown. Methods: We evaluated the effects of UST on histological and endoscopic activity in the UNIFI Ph3 induction study of UST in moderate–severe UC( n = 961). Two colonic biopsies were collected from distal colon at screening and induction Wk8. Subjects not in response to placebo (PBO) at Wk8 received UST 6 mg/kg IV, and those not in response to UST IV received UST 90 mg SC; biopsies were obtained at Wk16. Endoscopic healing (EH; also described a endoscopic improvement in the appearance of mucosa) was defined as a Mayo endoscopy score <1; histological healing (HH) comprised the following Geboes score-based criteria: absence of erosion or ulceration, absence of crypt destruction, and <5% of crypts with epithelial neutrophil infiltration. To encompass both macro- and microscopic scales, histo-endoscopic mucosal healing (HEMH) was defined as achieving both EH and HH. Results: At Wk8, EH was achieved in 26.6% and 13.8% of subjects treated with UST (combined 130 mg and 6 mg/kg IV doses)and PBO, respectively (adjusted tx difference, 12.8%; 95% CI, 7.9–17.8; p < 0.001). HH was achieved in 36.8% and 21.9% of UST and PBO-treated subjects, respectively (adjusted tx difference, 15.0%; 95% CI, 9.0–21.0; p < 0.001). Histo-endoscopic mucosal (HEMH) was achieved in 19.3% and 8.9% of UST and PBO-treated subjects, respectively (adjusted tx difference, 12.5%; 95% CI, 6.2–14.8; p < 0.001). Similar rates of EH, HH, and HEMH were achieved following induction with UST 130 mg or 6 mg/kg IV. Subjects not in response to PBO or UST at Wk8 were treated with UST at that time and re-evaluated at Wk16; of these, 12.1% and 16.5% of subjects who initially received UST or PBO IV, respectively, achieved HEMH. HH at Wk8 or Wk16 (irrespective of induction tx) was significantly associated with EH and HEMH ( p < 0.001) and with both absolute levels and post-tx changes in Mayo score, partial Mayo score, and Mayo symptom sub-scores for stool frequency and rectal bleeding. Conclusions: Among subjects with moderately–severely active UC, those receiving IV UST induction had higher rates of EH, HH, and HEMH than those receiving PBO. Approximately 10% of subjects who did not achieve clinical response 8 weeks after IV UST achieved HEMH following a second (SC) dose. HH is associated with reductions in clinical and endoscopic disease activity as well as patient-reported symptoms.